Manajemen Inovasi Pembelajaran untuk Meningkatkan Kualitas Pendidikan Dasar - Melina Sahriani; Netti Hardianti; Sabila Ramadani; Salwa Lazia; Kasman Kasman (Simpati, 2026)
This study examines the role of innovation management in learning to improve the quality of basic education, particularly in elementary schools. The background of this research is the increasing demand for adaptive, creative, and student-centered learning approaches in response to rapid educational changes in the digital era. The objective of this study is to analyze how the implementation of innovation management strategies in learning can enhance teaching effectiveness, student engagement, and overall educational quality. This research uses a qualitative descriptive method through literature review by analyzing relevant books, journals, and previous studies related to learning innovation and educational management. The findings indicate that effective management of learning innovation—such as the integration of technology, the use of active learning models, and teacher professional development—significantly contributes to improving student learning outcomes and classroom interaction. Furthermore, innovation management encourages teachers to be more creative in designing learning activities that are contextual and meaningful for students. The study implies that schools and education stakeholders need to strengthen institutional support, provide continuous training for teachers, and develop policies that encourage sustainable innovation in learning. Thus, structured innovation management in learning becomes a key factor in enhancing the quality of basic education in a competitive global era.